Précis of correspondence relating to Zanzibar affairs from 1856 to 1872. Prepared by Captain P D Henderson, attached to the Foreign Department - Henderson, P. D. (British Library, 1872)
The file is a précis of correspondence related to affairs at Zanzibar between the years 1856 and 1872, prepared by Captain Philip Durham Henderson of the Foreign Department in the Government of India. The contents of the précis, which includes reports from Christopher Palmer Rigby, the British Consul at Zanzibar, and Sir William Marcus Coghlan, relate to: the death in 1856 of the Sultan of Muscat Syed Saeed [Sa‘id bin Sulṭān al-Sa‘id] without a direct heir; the succession struggle between Syed Thoweynee [Thuwaynī bin Sa‘id al-Sa‘id] and Syed Majid [Sa‘id Majid bin Said al-Sa‘id]; British arbitration in the dispute; succession arrangements at Muscat and Zanzibar; the slave trade between Zanzibar and Muscat. The précis is organised into six chapters (labelled I to VI), as follows: I – Events preceding the arbitration by the Government of India; II – Arbitration of the Government of India; III – Proceedings subsequent to the arbitration relating to the question of subsidy; IV – Events at Zanzibar from the arbitration to the death of Syed Majid; V – Events in Zanzibar from the death of Syed Majid; VI – Slave Trade. The contents page lists four appendices (labelled A to D) that are not included in this copy of the précis.
Keywords: Zanzibar

Exploration géologique du Beni Mzab, du Sahara et de la région des steppes de la province d'Alger - Ville, Ludovic (Imprimerie nationale, 1872)
Keywords: Géologie -- Mzab